Effectiveness of Integrated Personnel and Payroll Information System in Addressing Ghost Worker Syndrome in Nigerian Public Sector (Global Journal of Human-Social Science, 2018)
The paper set out to examine the strategies adopted by Integrated Personnel and Payroll Information System (IPPIS) in addressing ghost worker syndrome in the Nigerian public sector. Furthermore, it critically looked at the effect of ghost worker on public service salary administration and also to analyse the challenges facing IPPIS in implementation of the policy in the Federal Inland Revenue Service in Nigeria. The paper utilised primary and secondary sources of data to elicit the opinions of public servants in the Federal Inland Revenue Service (FIRS). The study population (450) consists of senior and junior workers of administrative, finance and audit departments comprise the population of the study. The three departments are directly involved in human resources and salary administration in three senatorial districts in Lagos State, Nigeria. Interviews will be conducted with the three Directors and three Head of Departments to provides information on the challenges facing IPPIS in uploading check-off dues of the unions and cooperative, as well as detecting ghost workers on salary administration in FIRS .Secondary data were gather through the use of textbooks, academic journals, internet sources and IPPIS manuals. However, the finding revealed that the strategies adopted by IPPIS addresses ghost worker in the public sector in Nigeria. It also revealed that the introduction of IPPIS policy into the salary administration in Nigeria improved constant payment of employees. The study also revealed that there are still challenges facing IPPIS in uploading monthly salary of the employees.
Keywords: personnel; ghost workers; corruption; information system; salary administration